Antibacterial high-temperature-resistant PE (polyethylene) material and preparation process thereof

By blending high-density and medium-density polyethylene in polyethylene materials and adding SiOC aerogel composite silicon carbon-nitrogen fiber-loaded nanometal particles, the problem of bacterial growth in humid environments and degradation in high-temperature environments is solved, and the long-term antibacteriality and high-temperature resistance of the material are achieved.

CN119899447AInactive Publication Date: 2025-04-29GUANGZHOU AIYANG PLASTICS INDUSTRY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510269525.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2025-04-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polyethylene materials do not have antibacterial functions and are prone to bacterial growth in humid or organic polluted environments. Their thermal deformation temperature is low, making it difficult to meet the process needs of high-temperature sterilization and thermal filling.

Method used

High-density polyethylene and medium-density polyethylene are blended, and SiOC aerogel composite silicon carbon-nitrogen fibers are added to the material, which is loaded with nanosilver and/or nanosilver to improve the antibacterial properties of the material and high temperature resistance.

Benefits of technology

It realizes the long-term antibacteriality, high temperature resistance and processing stability of the material, and is suitable for high-end application fields such as medical packaging and high-temperature food containers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an antibacterial high-temperature-resistant PE (polyethylene) material and a preparation process thereof, and belongs to the technical field of polyethylene materials, the antibacterial high-temperature-resistant PE material comprises the following raw materials in parts by mass: 70-90 parts of high-density polyethylene, 10-30 parts of medium-density polyethylene, 5-9 parts of SiOC aerogel composite silicon-carbon-nitrogen fibers, 4-6 parts of a compatilizer, 0.1-1 part of an antioxidant and 6-8 parts of a plasticizer, the SiOC aerogel composite silicon carbon nitrogen fiber is loaded with nano-silver and / or nano-copper. The SiOC aerogel can amplify the enhancement effect of the silicon-carbon-nitrogen fiber on the mechanical property and heat resistance of the polyethylene material, improves the processability of the material, can provide a large number of loading sites for nano-silver and / or nano-copper, greatly prolongs the antibacterial period, and improves the antibacterial property of the polyethylene material. Oxidation inactivation of nano-silver and nano-copper in a high-temperature environment can be effectively avoided due to the high temperature resistance of the SiOC aerogel, and the high-mechanical-property polyethylene material with high temperature resistance and long-acting antibacterial property is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyethylene materials, and specifically relates to an antibacterial and high-temperature resistant PE material and a preparation process thereof. Background Art

[0002] Polyethylene (PE), as a widely used thermoplastic, is favored for its good processing performance, chemical stability and relatively low cost. However, with the development of modern technology and the improvement of people's living standards, the requirements for materials are becoming increasingly stringent, especially in the fields of medical treatment, food packaging, household appliances, etc., which put forward higher requirements for the antibacterial properties, high temperature resistance and mechanical strength of materials.

[0003] However, polyethylene material itself does not have antibacterial function and is prone to breed bacteria in humid or organically polluted environments, limiting its application in hygiene-sensitive fields such as food packaging and medical devices. In addition, ordinary polyethylene material has a low thermal deformation temperature and is prone to softening, deformation or degradation in high-temperature environments, making it difficult to meet process requirements such as high-temperature sterilization and hot filling.

[0004] In order to solve the above problems and meet market demand, most people choose to add antimicrobial agents or heat-resistant fillers to improve performance. However, the metal ions in the antimicrobial agents are easy to migrate, which will lead to insufficient antimicrobial durability, and the problem of agglomeration between nanoparticles is prominent. High-temperature dispersion will also cause the nano antimicrobial agents to be inactivated, making it difficult to withstand long-term hot and humid environments. Therefore, it is urgent to develop a multifunctional polyethylene material that has long-lasting antimicrobial properties, high temperature resistance, and processing stability to fill the technical gaps in high-end application fields such as medical packaging and high-temperature food containers. Summary of the invention

[0005] The object of the present invention is to provide an antibacterial and high temperature resistant PE material and a preparation process thereof, so as to obtain a multifunctional polyethylene material having both long-lasting antibacterial properties and high temperature resistance.

[0006] The purpose of the present invention can be achieved by the following technical solutions: In a first aspect, the present invention provides an antibacterial and high temperature resistant PE material, comprising the following raw materials in parts by weight: High-density polyethylene 70-90 parts; 10-30 parts of medium density polyethylene; 5-9 parts of SiOC aerogel composite silicon carbon nitrogen fiber; 4-6 parts of compatibilizer; Antioxidant 0.1-1 part; Plasticizer 6-8 parts; The SiOC aerogel composite silicon carbon nitride fiber is loaded with nano-silver and / or nano-copper.

[0007] Preferably, the compatibilizer includes a combination of one or more of polyethylene grafted with maleic anhydride, ethylene-propylene copolymer and maleic anhydride grafted with POE.

[0008] Preferably, the plasticizer includes a combination of one or more of polyolefin elastomer, hydrogenated styrene-butadiene block copolymer, styrene-butadiene-styrene block copolymer and ethylene propylene diene monomer rubber.

[0009] Preferably, the antioxidant includes antioxidant 1010, antioxidant 168, or a combination of one or more of the antioxidants.

[0010] By adopting the above technical scheme, the antibacterial and high temperature resistant PE material of the present invention adopts high-density polyethylene and medium-density polyethylene to blend, which can well combine the high strength, high rigidity, impact resistance of high-density polyethylene and the flexibility and processability of medium-density polyethylene to obtain a PE material with better mechanical properties. And with high-density polyethylene as the main body, the heat resistance of the base material can be better improved, and the addition of medium-density polyethylene can well regulate the defects of high melt viscosity and poor processability of high-density polyethylene, thereby obtaining a PE material with excellent mechanical properties and processability.

[0011] In order to improve the high temperature resistance and antibacterial properties of PE materials, the present invention adds SiOC aerogel composite silicon carbon nitrogen fiber to the PE material. Silicon carbon nitrogen fiber is a ternary ceramic fiber material, mainly composed of an amorphous Si-CN network structure, and has very excellent high temperature resistance and antioxidant properties and high strength. Adding it to polyethylene materials can greatly improve the heat resistance and mechanical properties of the materials, effectively improve the creep resistance of polyethylene materials, and compared with other ceramic fiber materials, such as silicon carbide fibers, it has better toughness, and can effectively improve the brittleness problem of ceramic fibers, thereby improving the heat resistance of the materials while improving the mechanical properties of the materials.

[0012] However, in the process of compounding with polyethylene materials, due to the high sintering temperature of silicon carbon nitride fibers, at the melting processing temperature of polyethylene materials, the high hardness of silicon carbon nitride fibers will bring great difficulties to processing. Increasing the temperature will easily lead to a large number of molecular chain breaks of the polyethylene material, resulting in a decrease in material performance. Moreover, since the surface of silicon carbon nitride fibers usually has polar groups and the interface bonding strength between the inorganic filler itself and the polyethylene organic polymer is not high, simply adding silicon carbon nitride fibers will cause the fibers to float to the surface, making it difficult to achieve a reinforcement effect.

[0013] Therefore, the surface of the silicon carbon nitride fiber of the present invention is also compounded with SiOC aerogel. Under the coating of SiOC aerogel, melt blending between the fiber and the polyethylene material can be achieved at a relatively low processing temperature. The nanoporous structure of SiOC aerogel can adsorb polyethylene molecular chains to form an interface transition layer, thereby improving the interface bonding force between the silicon carbon nitride fiber and the polyethylene matrix material, improving the processability while amplifying the enhancement effect of the silicon carbon nitride fiber on the mechanical properties and heat resistance of the polyethylene material. The composite of SiOC aerogel can also buffer the thermal stress caused by the large difference in thermal expansion coefficient between the polyethylene material and the silicon carbon nitride fiber, thereby greatly reducing the internal stress of the composite material. In addition, SiOC aerogel composite silicon carbon nitride fiber has a certain hydrophobicity and reduces the moisture absorption rate, which can not only improve the dispersibility of SiOC aerogel composite silicon carbon nitride fiber in the system, but also reduce the environment for bacterial growth, thereby enhancing the antibacterial property of the material.

[0014] Moreover, SiOC aerogel composite silicon carbon nitrogen fiber is also loaded with nanosilver and / or nanocopper. Both nanosilver and nanocopper can catalyze the production of reactive oxygen to attack bacterial biomacromolecules, including bacterial DNA, protein and lipid structures, thereby inducing cell apoptosis. They can also combine with the negative charges on the bacterial cell membrane to induce membrane potential imbalance and rupture, thereby increasing cell membrane permeability and leakage of contents, and further causing bacterial death.

[0015] The porous structure and high specific surface area of ​​SiOC aerogel provide a large number of loading sites for nanosilver and nanocopper, which can evenly disperse nanosilver or nanocopper particles, solving the problem of easy agglomeration of nanoparticles directly added to polymers. In addition, its pore structure can also achieve the slow release of nanosilver and nanocopper, thereby greatly extending the antibacterial cycle. The free carbon phase in SiOC aerogel can also enhance the efficiency of electron transfer, enhance the catalytic activity of nanosilver and nanocopper, and improve the efficiency of active oxygen generation, thereby improving the antibacterial efficiency. In addition, SiOC aerogel also has good high temperature resistance. As a physical support, it can meet the needs of high temperature resistant polyethylene materials on the one hand, and avoid the oxidative inactivation of nanosilver and nanocopper under high temperature environment on the other hand, thereby obtaining a high mechanical performance polyethylene material with both high temperature resistance and long-term antibacterial properties.

[0016] Preferably, the raw materials of SiOC aerogel include a carbon source, a silicon source and a water-soluble metal salt in a molar ratio of 1: (0.4-0.5): (0.15-0.2); the water-soluble metal salt includes a water-soluble silver salt and / or a water-soluble copper salt.

[0017] Preferably, the water-soluble silver salt includes one or a combination of silver nitrate, silver carbonate and silver sulfate.

[0018] Preferably, the water-soluble copper salt includes one or a combination of copper nitrate, copper chloride and copper sulfate.

[0019] Preferably, the carbon source includes a combination of one or more of methyltrimethoxysilane, phenyltrimethoxysilane, vinyltrimethoxysilane and dimethyldimethoxysilane.

[0020] Preferably, the silicon source includes a combination of one or more of ethyl orthosilicate, methyl orthosilicate, sodium silicate and silicon tetrachloride.

[0021] By adopting the above technical solution, the raw material of SiOC aerogel includes a carbon source, and the introduction of carbon atoms into the aerogel can enhance the strength of the obtained aerogel three-dimensional network structure, which is beneficial to the improvement of high temperature resistance, and not only enhances the material's antioxidant ability but also reduces the high-temperature creep rate of general oxides.

[0022] In addition, metal salts are introduced during the preparation of SiOC aerogels. The participation of metal salts in the preparation of aerogels can effectively avoid the agglomeration problem when nano-metal ions are directly mixed, so that nano-metal particles can be evenly distributed in the pores of the aerogels, reducing the distribution of surface nano-particles, maintaining the hydrophobicity of the obtained aerogels, and delaying the release rate of nano-particles, greatly improving the long-lasting antibacterial effect of polyethylene materials.

[0023] Preferably, the SiOC aerogel composite silicon carbon nitrogen fiber is prepared according to the following method: S1. The carbon source and the silicon source are stirred and dissolved in anhydrous ethanol to obtain a premixed solution, water is added dropwise to the premixed solution, and the pH value of the solution is adjusted to 2-3, and the reaction is stirred for 30-60 minutes, and then an aqueous solution of a water-soluble metal salt is added and the pH value of the solution is adjusted to 7-8, and the aerogel melt is obtained after stirring and polymerization for 4-6 hours; S2. The aerogel melt is coated on the silicon carbon nitride fiber, sealed and gel aged for 20 to 30 hours, and finally dried at 100 to 200° C. for 4 to 5 hours to obtain SiOC aerogel composite silicon carbon nitride fiber.

[0024] Preferably, the mass ratio of silicon carbon nitride fiber to aerogel melt is 1:(0.4-0.5).

[0025] Preferably, the molar ratio of water to carbon source in step S1 is (14-16):1.

[0026] By adopting the above technical scheme, with carbon source and silicon source as raw materials, a large amount of silicic acid and semi-silicic acid monomers can be produced by adding water for hydrolysis under acidic conditions, and then a metal salt aqueous solution is introduced to achieve uniform dispersion in the solution. Then, under alkaline conditions, the hydrolyzed monomers gradually undergo condensation polymerization to form small cross-linked bodies, which gradually accumulate to form a three-dimensional network SiOC aerogel. The obtained aerogel melt is coated on the surface of silicon carbon nitrogen fiber. When the gel is aged, the SiOC aerogel can penetrate into the fiber tightly and combine tightly with the fiber.

[0027] Preferably, the raw material further comprises 2 to 4 parts of a silane coupling agent; the silane coupling agent comprises one or a combination of an aminosilane coupling agent and a vinylsilane coupling agent.

[0028] More preferably, the aminosilane coupling agent includes a combination of one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β-aminoethyl-γ-aminopropyltrimethoxysilane, N-β-aminoethyl-γ-aminopropyltriethoxysilane and aminopropylmethyldiethoxysilane.

[0029] More preferably, the vinyl silane coupling agent includes a combination of one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(2-methoxyethoxy) silane and vinyl methyl dimethoxy silane.

[0030] By adopting the above technical solution, SiOC aerogel has a certain hydrophobicity, which can improve the ability of polyethylene materials to resist high temperature and humid heat environment. However, while SiOC aerogel has a certain hydrophobicity, it is not a non-polar substance. There are still groups such as silanol on the surface of SiOC aerogel, which will lead to unstable processing performance during the production process, and some fibers may migrate to the surface.

[0031] Therefore, silane coupling agents are also added to the polyethylene material. Aminosilane coupling agents and vinyl silane coupling agents can effectively improve the interfacial bonding between the polyethylene material and the SiOC aerogel composite silicon carbon nitrogen fiber, and can serve as a bridge to connect the two compounds, improve the dispersibility of the SiOC aerogel composite silicon carbon nitrogen fiber in the system, and further improve the mechanical properties of the material. Moreover, the addition of silane coupling agents can help the SiOC aerogel composite silicon carbon nitrogen fiber form a three-dimensional cross-linked network in the polyethylene material, thereby improving the high temperature resistance of the material and meeting application requirements including high temperature cooking.

[0032] In the second aspect, the present invention provides a preparation process of an antibacterial and high-temperature resistant PE material, comprising the following process steps: after mixing high-density polyethylene and medium-density polyethylene, other raw materials are added and continued to be mixed evenly to obtain a mixture; the mixture is melt-plasticized and extruded to granulate to obtain an antibacterial and high-temperature resistant PE material.

[0033] Preferably, the processing temperature of melt plasticization is 165-230°C.

[0034] Preferably, the technical effect of the present invention can be achieved without adding a silane coupling agent to the mixture.

[0035] Beneficial effects of the present invention: 1. The antibacterial and high temperature resistant PE material of the present invention is added with SiOC aerogel composite silicon carbon nitrogen fiber, which can effectively improve the heat resistance of the material. The composite SiOC aerogel can amplify the enhancement effect of silicon carbon nitrogen fiber on the mechanical properties and heat resistance of polyethylene materials, improve processing performance, and reduce moisture absorption rate; and can also provide a large number of loading sites for nanosilver and / or nanocopper to achieve their slow release, greatly extending the antibacterial cycle. The high temperature resistance of SiOC aerogel can also effectively avoid the oxidative inactivation of nanosilver and nanocopper in a high temperature environment, thereby obtaining a high mechanical property polyethylene material with both high temperature resistance and long-term antibacterial properties.

[0036] 2. The antibacterial and high temperature resistant PE material of the present invention also contains a silane coupling agent, which can improve the interfacial bonding force between the polyethylene material and the SiOC aerogel composite silicon carbon nitrogen fiber, increase the crosslinking density in the system, and thus enhance the high temperature resistance and mechanical properties of the material. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Preparation Example Preparation Example 1: A SiOC aerogel composite silicon carbon nitrogen fiber is prepared according to the following method: S1. 1 mol of vinyl trimethoxysilane and 0.45 mol of ethyl orthosilicate were stirred and dissolved in anhydrous ethanol to obtain a premixed solution, 270 g of water was added dropwise to the premixed solution, and the pH value of the solution was adjusted to 3. After stirring and reacting for 40 minutes, a 20% by mass fraction of silver nitrate aqueous solution (the amount of silver nitrate added was 0.18 mol) was added and the pH value of the solution was adjusted to 7.5. After stirring and polymerizing for 5 hours, an aerogel melt was obtained; S2. The aerogel melt was coated with silicon carbon nitride fiber (diameter of 10-12 μm), wherein the mass ratio of silicon carbon nitride fiber to aerogel melt was 1:0.5, and the aerogel was sealed for gel aging for 24 hours, and finally dried at 150°C for 5 hours to obtain SiOC aerogel composite silicon carbon nitride fiber.

[0039] Preparation Example 2, a SiOC aerogel composite silicon carbon nitrogen fiber, is different from Preparation Example 1 only in that the added amount of tetraethyl orthosilicate is 0.4 mol; the added amount of silver nitrate is 0.2 mol.

[0040] Preparation Example 3, a SiOC aerogel composite silicon carbon nitrogen fiber, is different from Preparation Example 1 only in that the added amount of tetraethyl orthosilicate is 0.5 mol; the added amount of silver nitrate is 0.15 mol.

[0041] Preparation Example 4, a SiOC aerogel composite silicon carbon nitride fiber, is different from Preparation Example 1 only in that the mass ratio of silicon carbon nitride fiber to aerogel melt is 1:0.4.

[0042] Preparation Example 5, a SiOC aerogel composite silicon carbon nitride fiber, is different from Preparation Example 1 only in that an equal amount of copper nitrate is used to replace silver nitrate.

[0043] Preparation Example 6, a SiOC aerogel composite silicon carbon nitride fiber, is different from Preparation Example 1 only in that silver nitrate is replaced by a mixture of equal amounts of silver nitrate and copper nitrate in a mass ratio of 1:1.

[0044] Preparation Example 7, a SiOC aerogel composite silicon carbon nitride fiber, is different from Preparation Example 1 only in that the mass ratio of silicon carbon nitride fiber to aerogel melt is 1:0.2.

[0045] Preparation Example 8, a SiOC aerogel composite silicon carbon nitride fiber, is different from Preparation Example 1 only in that the mass ratio of silicon carbon nitride fiber to aerogel melt is 1:0.7.

[0046] Preparation Example 9, a SiOC aerogel composite silicon carbon nitrogen fiber, is prepared according to the following method: S1. 1 mol of vinyl trimethoxysilane and 0.45 mol of ethyl orthosilicate were stirred and dissolved in anhydrous ethanol to obtain a premixed solution, 270 g of water was added dropwise to the premixed solution, and the pH value of the solution was adjusted to 3. After stirring and reacting for 40 min, the pH value of the solution was adjusted to 7.5, and the aerogel melt was obtained after stirring and polymerization for 5 h; S2. The aerogel melt was mixed with a silver nitrate aqueous solution with a mass fraction of 20% (the amount of silver nitrate added was 0.18 mol) and coated with silicon carbon nitride fibers (diameter of 10-12 μm), wherein the mass ratio of silicon carbon nitride fibers to aerogel melt was 1:0.5, and the gel was sealed for aging for 24 hours, and finally dried at 150°C for 5 hours to obtain SiOC aerogel composite silicon carbon nitride fibers.

[0047] Preparation Example 10, a SiOC aerogel composite silicon carbon nitrogen fiber, is prepared according to the following method: S1. 1 mol of vinyl trimethoxysilane and 0.45 mol of ethyl orthosilicate were stirred and dissolved in anhydrous ethanol to obtain a premixed solution, 270 g of water was added dropwise to the premixed solution, and the pH value of the solution was adjusted to 3. After stirring and reacting for 40 min, the pH value of the solution was adjusted to 7.5, and the aerogel melt was obtained after stirring and polymerization for 5 h; S2. The aerogel melt was coated with silicon carbon nitride fiber (diameter of 10-12 μm), wherein the mass ratio of silicon carbon nitride fiber to aerogel melt was 1:0.5, and the aerogel was sealed for gel aging for 24 hours, and finally dried at 150°C for 5 hours to obtain SiOC aerogel composite silicon carbon nitride fiber.

[0048] Preparation Example 11, a SiOC aerogel composite silicon carbide fiber, is different from Preparation Example 1 only in that an equal amount of silicon carbide fiber is used to replace the silicon carbon nitrogen fiber.

[0049] Preparation Example 12: A cellulose aerogel composite silicon carbon nitrogen fiber is prepared according to the following method: S1. Dissolve 9g of sodium hydroxide and 1g of polyethylene glycol in 90g of purified water, add 1g of cellulose to the solution, and stir at room temperature for 3h; then, cool the mixed solution to -10℃ and freeze it at this temperature for 12h to obtain a frozen solid; thaw at room temperature and stir vigorously for 30 min to obtain a uniform cellulose solution; freeze the uniform cellulose solution at -10℃ for 12h to set, then replace it with 1% hydrochloric acid, distilled water and tert-butyl alcohol in turn to obtain a white hydrogel, freeze-dry the hydrogel to prepare a porous cellulose aerogel; soak the porous cellulose aerogel in 200ml of 0.005 mol / L silver nitrate solution for 12h. Finally, add 0.4g of sodium hydroxide and stir thoroughly to obtain an aerogel melt; S2. The aerogel melt was coated with silicon carbon nitride fibers (diameter of 10-12 μm), wherein the mass ratio of silicon carbon nitride fibers to aerogel melt was 1:0.5, and the aerogel was sealed for gel aging for 24 h, and finally dried at 150°C for 5 h to obtain cellulose aerogel composite silicon carbon nitride fibers.

[0050] Example Example 1, an antibacterial and heat-resistant PE material, is prepared according to the following process steps: 8 kg of high-density polyethylene and 2 kg of medium-density polyethylene were mixed, and then 0.7 kg of SiOC aerogel composite silicon carbon nitrogen fiber prepared in Preparation Example 1, 0.5 kg of polyethylene grafted maleic anhydride, 0.05 kg of antioxidant 1010 and 0.7 kg of POE (model: ENGAGE™ 8402) were added and mixed to obtain a mixture; The mixture is melt-plasticized and extruded into granules to obtain an antibacterial and high-temperature resistant PE material, wherein the melt-plasticization temperature is 180-220°C.

[0051] Example 2, an antibacterial and heat-resistant PE material, is prepared according to the following process steps: 7 kg of high-density polyethylene and 3 kg of medium-density polyethylene were mixed, and then 0.7 kg of SiOC aerogel composite silicon carbon nitrogen fiber prepared in Preparation Example 2, 0.5 kg of polyethylene grafted maleic anhydride, 0.05 kg of antioxidant 1010 and 0.6 kg of POE (model: ENGAGE™ 8402) were added and mixed to obtain a mixture; The mixture is melt-plasticized and extruded into granules to obtain an antibacterial and high-temperature resistant PE material, wherein the melt-plasticization temperature is 180-220°C.

[0052] Example 3, an antibacterial and heat-resistant PE material, prepared according to the following process steps: 9 kg of high-density polyethylene and 1 kg of medium-density polyethylene were mixed, and then 0.7 kg of SiOC aerogel composite silicon carbon nitrogen fiber prepared in Preparation Example 3, 0.5 kg of polyethylene grafted maleic anhydride, 0.05 kg of antioxidant 1010 and 0.8 kg of POE (model: ENGAGE™ 8402) were added and mixed to obtain a mixture; The mixture is melt-plasticized and extruded into granules to obtain an antibacterial and high-temperature resistant PE material, wherein the melt-plasticization temperature is 180-220°C.

[0053] Example 4, an antibacterial and heat-resistant PE material, is different from Example 1 only in that the added amount of the SiOC aerogel composite silicon carbon nitrogen fiber prepared in Preparation Example 1 is 0.5 kg; and the added amount of polyethylene grafted maleic anhydride is 0.4 kg.

[0054] Example 5, an antibacterial and heat-resistant PE material, is different from Example 1 only in that the added amount of the SiOC aerogel composite silicon carbon nitrogen fiber prepared in Preparation Example 1 is 0.9 kg; and the added amount of polyethylene grafted maleic anhydride is 0.6 kg.

[0055] Example 6, an antibacterial and heat-resistant PE material, is different from Example 1 only in that an equal amount of SiOC aerogel composite silicon carbon nitride fibers prepared in Preparation Example 4 is used to replace the SiOC aerogel composite silicon carbon nitride fibers prepared in Preparation Example 1.

[0056] Example 7, an antibacterial and heat-resistant PE material, is different from Example 1 only in that an equal amount of SiOC aerogel composite silicon carbon nitride fibers prepared in Preparation Example 5 are used to replace the SiOC aerogel composite silicon carbon nitride fibers prepared in Preparation Example 1.

[0057] Example 8, an antibacterial and heat-resistant PE material, differs from Example 1 only in that an equal amount of SiOC aerogel composite silicon carbon nitride fibers prepared in Preparation Example 6 are used to replace the SiOC aerogel composite silicon carbon nitride fibers prepared in Preparation Example 1.

[0058] Example 9, an antibacterial and heat-resistant PE material, differs from Example 1 only in that an equal amount of SiOC aerogel composite silicon carbon nitride fibers prepared in Preparation Example 7 is used to replace the SiOC aerogel composite silicon carbon nitride fibers prepared in Preparation Example 1.

[0059] Example 10, an antibacterial and heat-resistant PE material, is different from Example 1 only in that an equal amount of SiOC aerogel composite silicon carbon nitride fibers prepared in Preparation Example 8 is used to replace the SiOC aerogel composite silicon carbon nitride fibers prepared in Preparation Example 1.

[0060] Example 11, an antibacterial and heat-resistant PE material, is different from Example 1 only in that 0.3 kg of vinyl triethoxysilane is further added to the mixture.

[0061] Example 12, an antibacterial and heat-resistant PE material, is different from Example 1 only in that 0.3 kg of γ-aminopropyltriethoxysilane is also added to the mixture.

[0062] Comparative Example Comparative Example 1, an antibacterial and heat-resistant PE material, is different from Example 1 only in that the added amount of the SiOC aerogel composite silicon carbon nitrogen fiber prepared in Preparation Example 1 is 0.2 kg.

[0063] Comparative Example 2, an antibacterial and heat-resistant PE material, is different from Example 1 only in that the added amount of the SiOC aerogel composite silicon carbon nitrogen fiber prepared in Preparation Example 1 is 1.2 kg.

[0064] Comparative Example 3, an antibacterial and heat-resistant PE material, differs from Example 1 only in that an equal amount of SiOC aerogel composite silicon carbon nitride fibers prepared in Preparation Example 9 is used to replace the SiOC aerogel composite silicon carbon nitride fibers prepared in Preparation Example 1.

[0065] Comparative Example 4, an antibacterial and heat-resistant PE material, differs from Example 1 only in that the SiOC aerogel composite silicon carbon nitride fiber prepared in Preparation Example 1 is replaced with an equal amount of SiOC aerogel composite silicon carbon nitride fiber prepared in Preparation Example 10, and 20 g of nanosilver particles are added to the mixture.

[0066] Comparative Example 5, an antibacterial and heat-resistant PE material, differs from Example 1 only in that an equal amount of SiOC aerogel composite silicon carbide fiber prepared in Preparation Example 11 is used to replace the SiOC aerogel composite silicon carbon nitrogen fiber prepared in Preparation Example 1.

[0067] Comparative Example 6, an antibacterial and heat-resistant PE material, differs from Example 1 only in that an equal amount of cellulose aerogel composite silicon carbon nitride fiber prepared in Preparation Example 12 is used to replace the SiOC aerogel composite silicon carbon nitride fiber prepared in Preparation Example 1.

[0068] Comparative Example 7, an antibacterial and heat-resistant PE material, is different from Example 1 only in that medium-density polyethylene is not added and the added amount of high-density polyethylene is 10 kg.

[0069] Comparative Example 8, an antibacterial and heat-resistant PE material, is different from Example 1 only in that high-density polyethylene is not added and the amount of medium-density polyethylene added is 10 kg.

[0070] Comparative Example 9, an antibacterial and heat-resistant PE material, differs from Example 1 only in that the SiOC aerogel composite silicon carbon nitride fiber prepared in Preparation Example 1 is replaced with an equal amount of silicon carbon nitride fiber that has not been composite-modified, and 20 g of nanosilver particles are added to the mixture.

[0071] Performance testing 1. Mechanical properties test: (1) According to the relevant records in GB / T 1040.1-2018 "Determination of tensile properties of plastics Part 1: General principles", the tensile properties of the antibacterial and high temperature resistant PE materials obtained in the examples and comparative examples were tested; (2) According to the relevant records in GB / T 1043.1-2008 "Determination of impact properties of simply supported beams of plastics Part 1: Non-instrumented impact test", the impact resistance of the antibacterial and high temperature resistant PE materials obtained in the examples and comparative examples was tested.

[0072] 2. Heat resistance test: According to the relevant records in GB / T 1634.1-2019 "Determination of load deformation temperature of plastics Part 1: General test method", the heat deformation temperature of the antibacterial and high temperature resistant PE materials obtained in the examples and comparative examples was tested.

[0073] The above test results are shown in Table 1.

[0074] 3. Antibacterial test: (1) According to the relevant records in GB / T 31402-2015 "Test Method for Antibacterial Performance of Plastic Surfaces", the antibacterial properties of the antibacterial and high temperature resistant PE materials obtained in the examples and comparative examples were tested; (2) The antibacterial and high temperature resistant PE materials obtained in the examples and comparative examples were placed at 150°C for 1 day, and then the antibacterial properties of the materials were tested.

[0075] The above test results are shown in Table 2.

[0076] Table 1 Mechanical properties and heat resistance test results

[0077] Table 2 Antibacterial performance test results

[0078] According to Table 1 and Table 2, in combination with Example 1, Example 9, Example 10 and Comparative Example 9, it can be seen that the mechanical properties, heat deformation temperature, antibacterial rate and antibacterial rate after high temperature treatment of Example 9, Example 10 and Comparative Example 9 are all reduced compared with those of Example 1. The reason is that the difference between Example 9, Example 10 and Comparative Example 9 and Example 1 is only that the content of SiOC aerogel compounded on the surface of the silicon carbon nitride fiber is adjusted. In Example 9, the compounding amount of SiOC aerogel is reduced, which will directly affect the interface bonding force between the silicon carbon nitride fiber and the polyethylene matrix, the processing performance of the material is reduced, the internal stress of the material is increased, and the impact resistance is reduced. In addition, as the amount is reduced, the antibacterial active substance is reduced, and the antibacterial performance is also reduced. In Comparative Example 9, no SiOC aerogel is compounded, and the performance degradation is more obvious; in Example 10, the compounding amount of SiOC aerogel is increased, which will cause the aerogel to be densely packed, greatly destroy the flexibility of the material, and cause the mechanical properties of the material to decrease.

[0079] Combining Example 1, Example 11 and Example 12, it can be seen that the various properties of Example 11 and Example 12 are slightly enhanced compared with Example 1. The reason is that a silane coupling agent is also added to Example 11 and Example 12, which can improve the interface bonding force between SiOC aerogel composite silicon carbon nitrogen fiber and polyethylene, and increase the crosslinking density in the system, thereby improving the heat resistance of the material. At high temperatures, the activity of the antibacterial active substance, namely nanosilver or nanocopper, can be better protected, thereby improving the antibacterial property of the material in a high temperature environment.

[0080] Combining Example 1, Comparative Example 3 and Comparative Example 4, it can be seen that the various properties of Comparative Example 3 and Comparative Example 4 are all reduced compared with Example 1. The reason is that the metal salt in Comparative Example 3 is blended and added after the aerogel polycondensation, and most of it is concentrated on the surface of SiOC aerogel, which will not only increase the polarity of SiOC aerogel composite silicon carbon nitrogen fiber and reduce the dispersibility in polyethylene materials, but also be oxidized and inactivated during high-temperature treatment, and lose the antibacterial effect, so the antibacterial property is significantly reduced after high-temperature treatment. The antibacterial active substance in Comparative Example 4 is directly mixed in the polyethylene material, lacking the loading effect of SiOC aerogel. In the polyethylene material, nanosilver or nanocopper is very easy to agglomerate, which affects the antibacterial activity and causes stress concentration, reduces the mechanical properties of the material, and cannot resist the influence of high temperature well.

[0081] In combination with Example 1, Comparative Example 5 and Comparative Example 6, it can be seen that the various properties of Comparative Example 5 and Comparative Example 6 are reduced compared with Example 1. The reason is that in Comparative Example 5, silicon carbide fiber is used to replace silicon carbon nitrogen fiber, and its rigidity is increased. During the process of blending and melt extrusion with polyethylene, the structure is damaged, and the enhancement effect on the mechanical properties of the material is greatly reduced; in Comparative Example 6, cellulose aerogel is used to replace SiOC aerogel. The temperature resistance of cellulose aerogel is limited and it cannot maintain the antibacterial activity in a long-term high temperature environment. In addition, the cellulose aerogel has strong polarity, poor dispersibility in polyethylene material, and weak interface bonding force, which leads to a decrease in the mechanical properties of the material.

[0082] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An antibacterial and high temperature resistant PE material, characterized in that: Including the following raw materials by mass: High-density polyethylene 70-90 parts; 10-30 parts of medium density polyethylene; 5-9 parts of SiOC aerogel composite silicon carbon nitrogen fiber; 4-6 parts of compatibilizer; Antioxidant 0.1-1 part; Plasticizer 6-8 parts; The SiOC aerogel composite silicon carbon nitride fiber is loaded with nano-silver and / or nano-copper.

2. The antibacterial and high temperature resistant PE material according to claim 1, characterized in that: The raw materials of the SiOC aerogel include a carbon source, a silicon source and a water-soluble metal salt in a molar ratio of 1: (0.4-0.5): (0.15-0.2); the water-soluble metal salt includes a water-soluble silver salt and / or a water-soluble copper salt.

3. The antibacterial and high temperature resistant PE material according to claim 2, characterized in that: The carbon source includes one or more of methyltrimethoxysilane, phenyltrimethoxysilane, vinyltrimethoxysilane and dimethyldimethoxysilane.

4. The antibacterial and high temperature resistant PE material according to claim 2, characterized in that: The silicon source includes one or more of ethyl orthosilicate, methyl orthosilicate, sodium silicate and silicon tetrachloride.

5. The antibacterial and high temperature resistant PE material according to claim 2, characterized in that: The SiOC aerogel composite silicon carbon nitrogen fiber is prepared according to the following method: S1. The carbon source and the silicon source are stirred and dissolved in anhydrous ethanol to obtain a premixed solution, water is added dropwise to the premixed solution, and the pH value of the solution is adjusted to 2-3, and the reaction is stirred for 30-60 minutes, and then an aqueous solution of a water-soluble metal salt is added and the pH value of the solution is adjusted to 7-8, and the aerogel melt is obtained after stirring and polymerization for 4-6 hours; S2. The aerogel melt is coated on the silicon carbon nitride fiber, sealed and gel aged for 20 to 30 hours, and finally dried at 100 to 200° C. for 4 to 5 hours to obtain SiOC aerogel composite silicon carbon nitride fiber.

6. The antibacterial and high temperature resistant PE material according to claim 5, characterized in that: The mass ratio of the silicon carbon nitride fiber to the aerogel melt is 1:(0.4-0.5).

7. The antibacterial and high temperature resistant PE material according to claim 1, characterized in that: The raw materials also include 2 to 4 portions of silane coupling agents; the silane coupling agents include one or a combination of two of aminosilane coupling agents and vinylsilane coupling agents.

8. The antibacterial and high temperature resistant PE material according to claim 1, characterized in that: The compatibilizer includes one or more combinations of polyethylene grafted with maleic anhydride, ethylene-propylene copolymer and maleic anhydride grafted with POE.

9. The antibacterial and high temperature resistant PE material according to claim 1, characterized in that: The plasticizer includes one or more of a polyolefin elastomer, a hydrogenated styrene-butadiene block copolymer, a styrene-butadiene-styrene block copolymer and an ethylene propylene diene monomer rubber.

10. A process for preparing an antibacterial and high temperature resistant PE material according to any one of claims 1 to 9, characterized in that: The process steps include: After the high-density polyethylene and the medium-density polyethylene are mixed, other raw materials are added and continued to be mixed evenly to obtain a mixture; the mixture is melt-plasticized and extruded into granules to obtain an antibacterial and high-temperature resistant PE material.